2D Material Disassembly: Disassembly of 2D Vertical Heterostructures (Adv. Mater. 4/2019). Issue 4 (22nd January 2019) - Xiao, Yao; Zhang, Tao; Zhou, Mengyue; Weng, Zheng; Chang, Xuejiao; Yang, Kena; Liu, Jinglu; Li, Juntao; Wei, Bin; Wang, Zhongchang; Fu, Lei
Abstract : In article number1805976, Lei Fu and co‐workers demonstrate the disassembly of 2D vertical heterostructures with the activation of specific disassembly promoters (DPs) and the weakening of the interlayer van der Waals interaction, which initially establishes the inverse process to 2D material assembly. The unique disassembly process has remarkable prospects toward the modification and functionalization of 2D materials, which opens up a novel pathway to functionally integrated devices.